Professional Scrum with Team Foundation Server 2010 - Resnick, Steve; Bjork, Aaron; De la Maza, Michael (Indianapolis, IN : Wiley Pub., 2011)
Provides information on using Visual Studio Team Foundation Server to execute a Scrum project, covering such topics as software project management, the tracking and reporting functions of TFS, using Scrum artifacts, creating product backlog items, and running a release.
"Programmer to programmer"--Cover.
Includes bibliographical references (p. [289]) and index.
Keywords: Microsoft Visual studio; Microsoft Visual Studio (Computer software); Agile software development; Scrum (Computer software development); Computer software -- Design; Scrum (Computer software development)